2019
DOI: 10.3389/fonc.2019.01284
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Colorectal Cancer: The Role of Translational Proteomics Research

Abstract: Colorectal cancer is one of the most common cancers in the world, and it is one of the leading causes of cancer-related death. Despite recent progress in the development of screening programs and in the management of patients with colorectal cancer, there are still many gaps to fill, ranging from the prevention and early diagnosis to the determination of prognosis factors and treatment of metastatic disease, to establish a personalized approach. The genetic profile approach has been increasingly used in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 91 publications
0
80
0
Order By: Relevance
“…Several blood-based biomarkers, including carcioembriogenic antigen (CEA) and carbohydrate antigen (CA) 19-9 are well established in clinical practice, howbeit, low specificity and sensitivity are key limitations of these tests (10). Recent advances in -omics technologies enabled discovery of new potential biomarkers, including different proteins (11), circulating tumor DNA (12,13) or microRNA (14) and circulating tumor cells (15) as well as numerous metabolites (16,17) and transcriptional biomarkers (18). Despite many of these biomarkers demonstrated high diagnostic potential in retrospective proof-of-concept studies, further research is required to determine their clinical validity and utility (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several blood-based biomarkers, including carcioembriogenic antigen (CEA) and carbohydrate antigen (CA) 19-9 are well established in clinical practice, howbeit, low specificity and sensitivity are key limitations of these tests (10). Recent advances in -omics technologies enabled discovery of new potential biomarkers, including different proteins (11), circulating tumor DNA (12,13) or microRNA (14) and circulating tumor cells (15) as well as numerous metabolites (16,17) and transcriptional biomarkers (18). Despite many of these biomarkers demonstrated high diagnostic potential in retrospective proof-of-concept studies, further research is required to determine their clinical validity and utility (11).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in -omics technologies enabled discovery of new potential biomarkers, including different proteins (11), circulating tumor DNA (12,13) or microRNA (14) and circulating tumor cells (15) as well as numerous metabolites (16,17) and transcriptional biomarkers (18). Despite many of these biomarkers demonstrated high diagnostic potential in retrospective proof-of-concept studies, further research is required to determine their clinical validity and utility (11). Another challenges, limiting extensive use of these biomarkers in routine practice nowadays, are their expensiveness and lack of reproducibility (11).…”
Section: Introductionmentioning
confidence: 99%
“…summarizes clinical studies in CRC patients. It is well-recognized that CRC screening and monitoring strategies such as diagnosis and elimination of premalignant lesions and adenomatous polyps result in reduction of CRC mortality(157). Several clinical studies have pursued to carry out biomarkers that could be identified as potent metastasis diagnosis in patients with colorectal cancer.Kuniyasu et al in 2003 have investigated 119 non-diabetic patients with CRC, who found out RAGE expression was increased in 55% of the cases.…”
mentioning
confidence: 99%
“…Moreover, molecular indicators can be grouped into three classes: prognostic, predictive and diagnostic markers [ 12 ]. Prognostic markers indicate the possible progression of the disease, such as: adenomatous polyposis coli (almost 100% of individuals develop CRC with this germ line mutation) [ 13 , 14 ], p53 (tumor suppressor p53 expression) [ 12 ], and epidermal growth factor receptor (EGFR; up to 80% over expression in CRC) [ 15 ]. Predictive indicators are used to foresee treatment measures to be taken on a patient.…”
Section: Introductionmentioning
confidence: 99%